The New Testament in Greek IV. The Gospel According to St. John : 1. The Papyri - Parker,; Elliott, (New Testament Tools, Studies and Documents ;, 1995)
This first stage of the IGNTP John provides the evidence of the 23 papyri. The material is presented in three ways. The first section provides transcriptions of the witnesses, with notes recording difficulties and differences from earlier transcriptions. The second provides a complete apparatus criticus . For each verse there is a record of the extent of the papyri available for it, and a list of all divergences from the collating base. The third section provides a complete set of plates of all the papyri except p66 and p75. There is a detailed introduction, and there are sections on dating and the comparative extent of the papyri. Bringing all this material together for the first time, this edition presents a number of new features in the editing of New Testament witnesses.